Oral precursor lesions and malignant transformation – who, where, what, and when?. Issue 9 (November 2015) - Goodson, M.L.; Sloan, P.; Robinson, C.M.; Cocks, K.; Thomson, P.J.
Abstract: Oral potentially malignant disorders (PMD) are recognisable mucosal conditions that have an unpredictable risk of transformation to squamous cell carcinoma (SCC), a lethal and deforming disease of rising incidence. Contemporary management is based on clinical recognition of suspicious lesions and incisional biopsy to enable histopathological assessment and grading of dysplasia, together with excision of high-risk lesions and long-term surveillance. However, it is impossible to predict clinical outcome or risk of malignant transformation. Our aim was to evaluate the relevance of previously identified oral precursor lesions for the development of SCC and staging of disease. We therefore retrospectively reviewed 1248 cases of SCC diagnosed in oral and maxillofacial surgery units at Newcastle upon Tyne and Sunderland hospitals between 1996 and 2009. Of them, 58 identifiable precursor lesions became malignant but only 25 had been dysplastic on initial biopsy; 19 of 33 non-dysplastic lesions exhibited lichenoid inflammation only. SCC arose most often on the ventrolateral tongue and floor of the mouth, with a mean transformation time of 29.2 months. Transformation time was significantly shorter in men (p = 0.018) and those over 70 years of age (p = 0.010). Patients who consumed more than 21 units of alcohol/week and those who had had interventional laser surgery to treat precursor lesions, had higher-staged tumours (p = 0.048). Although retrospective, this study shows that the results of incisional biopsy and grading of dysplasia have limited use as predictive tools, and supports the view that cancer may arise in the absence of recognisable epithelial dysplasia. Our findings confirm the importance of clinical vigilance and active surveillance in the management of all patients with clinically suspicious oral lesions, irrespective of the histological findings.